DOMESTIC VIOLENCE TOWARDS BLACK AMERICAN WOMEN IN THE SOUTH DURING 1970s-1980s AS SEEN IN ALICE WALKER’S “THE COLOR PURPLE” - Bay, Jenny Ronawati; Loda, Wihelmina H (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2023)
This Article presented an analysis of the domestic violence towards black American women as seen in Alice Walker novel “The Color Purple”. The reason for particularly choose this topic because the wants to find out how the domestic violence faced by black American women during 1970s- 1980s delineated in “The Color Purple”. In this article, the writers applied library research to collect the data. The main data were taken from the novel “The Color Purple” by Alice Walker. Furthermore, in this article, the writers used the sociology of literature theory since the writers analyzes the novel as a reflection of situation that happened to black American women in the south during 1970s- 1980s. After analyzing the data, the writers found out that domestic violence happened to the two characters in the novel: Celie and Sofia. The black women in the novel represented black American women in the South during 1970s- 1980s. They undergo domestic violence from black American men. The violences were: physical violence, mental violence and neglect.